Hydraulic Evaluation on 17 ½ inch Hole in Directional Well Y-1, Field Y Using BHHP Method - Apriandi Rizkina Rangga Wastu; Henry David Young; Lilik Zabidi; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2022)
The evaluation of hydraulics carried out in a trajectory namely 17 ½ inches provides an overview of the hydraulic problems that occur with less-than-optimal pressure in the bit because it is less than the minimum percentage value that should be. which is less than 50%. it is affected by factors such as flow rate. mud weight. the rheology of the mud used and pressure loss both in the surface and sub-surface such as bit. pipe and annulus. So, optimization with the BHHP (Bit Hydraulic Horse Power) method becomes the next step to be taken in order for the drilling operation can perform better. It has been found from the optimization results that the CTR (Cutting Transport Ratio) method is a cutting analysis method that demonstrates the correct performance of the cutting transport process if the minimum percentage of 50% or higher is met. In addition, this method also takes the angle of inclination of a directional well Y-1 into one of the considerations. On the first trajectory. 17 ½ inch hole (1338.58 – 3166.01 ft) the pressure in the bit increased from around 22.83% to 31.14% at the initial condition to 56.20% until 56.59% with cutting transport results after being optimized up to 99%. The use of the BHHP (Bit Hydraulic Horse Power) method to optimize drilling hydraulics in the directional well is said to be successful because it produces an optimization value that is greater than the minimum standard which is 50%. Furthermore, the CTR (Cutting Transport Ratio) method to analyze the transport of cuttings to the surface has been running well showing the results that the cuttings have been successfully transported to the surface. Therefore, this method can be said to be successful with the acquisition of a value percentage above 50%.